Memórias “Bilaquianas” – o Instituto Estadual de Educação Olavo Bilac na constituição docente de professoras - Gomes, Adriana Cristina (2018)
This essay named “Bilaquianas’” memories – Olavo Bilac State Institute of Education in the educational constitution of teachers, is inserted in the research field of Pedagogic Management and Educational Contexts from the graduation program in Public Politics and Educational management, professional master’s degree of Santa Maria Federal University. The present investigation was oriented by the following purpose: comprehending the movement of educational formation and the histories told by teachers who took the licensing course and turned into teachers responsible for other educators’ instruction.The aim was to comprehend the formative movement through the histories narrated by teachers that have taken the teachers’ licensing course and who acted or have been acting as other teachers’ instructors. The key question was: In which way taken the teachers’ licensing course has interfered in the professional and personal trajectory of instructor teachers certified by Olavo Bilac State Institute of Education? The research was qualitative, having a self-biographical and also a narrative analysis approach. The subjects of this analysis were four educators certified by the teachers’ licensing course, who after obtaining the prior formation, have started dedicating themselves to the formation of other teachers. Narrative interviews were performed, besides the writing of reminiscent texts which served as basis for the narrative analysis; that enabled to rescue the formative memories of each participant teacher of this research, as well as their “Bilaquiana Identity”, which being restored, resulted in the process of recognition of the sense of belonging and affective bond with the institution and the reflexive formation. The research revealed the resonance of the teachers’ licensing course formation and the narratives of the ones previously known as “normalistas”, their path in the bilaquiano’s trajectory, as well as its influence in their professional choices. Thus and so, the reader is invited to know and comprehend the meaning of Bilaquiana’s memories and the formative processes of instructor teachers who initiated their teaching practice in the teachers’ licensing course over the last fifty years. It is introduced as a product of the professional Master’s degree research the elaboration of an e-book reuniting all the narratives. The relevance of this study is evidenced in the inherent history of education in Santa Maria and in the state of Rio Grande do Sul, taken the fact that Olavo Bilac State Institute of Education was a reference in the teachers’ instruction for over a century and influenced the constitution of the professional identity in this place.